Proust and Benjamin: the Invisible Image - Beryl Schlossman (Studies in 20th & 21st Century Literature, 1986)
Benjamin's essay "Zum Bilde Prousts" questions the status of the image even as it leafs through the possibilities and variations that form it—as photograph, figure, representation, disappearing trace or promise of creation. As the image of Proust's novel, Benjamin's text takes up the elements of A la Recherche du temps perdu (poetic language, autobiography, critical commentary) in the terms of Benjamin's theory of allegory reflected through the Proustian strategy of reading and writing. "Zum Bilde Prousts" examines the traditional markers of "art" and "life," locating Proustian recherche—and Benjamin's image—in the deep waters beyond them. Through an interpretation of Benjamin's image of Proustian ecstasy (the descent of the mystic) and the images unfolded "Au Temps Perdu" (Benjamin's mystical station of nineteenth-century allegory), Benjamin's essay sollicits a new reading of time and eternity, memory and ecstasy. The final illumination of Proust's artful night indicates the decisive turn toward writing at the spot where "Niles of language" come together—the point of convergence of the image and its invisibility.
Keywords: Zum Bilde Prousts; Walter Benjamin; status; image; photograph; figure; representation; creation; A la Recherche du temps perdu; poetic language; autobiography; critical commentary; allegory; Proust; art; life; recherche; ecstasy; Proustian ecstasy; Au Temps Perdu; time; eternity; memory